Risk, safety and consent in contemporary blood services in the United Kingdom: perspectives from sociology and law - Busby, Helen (UK Data Service, 2013)
This project aims to provide a sociologically informed analysis of professional practice, public policy, law, and public understandings in relation to risks in the supply of blood products in the UK. Blood is a staple of the supply of biological materials that underpin contemporary medical practice and, contrary to the older images of blood banking, plasma-derived products manufactured by pharmaceutical companies form an important part of the blood supply. A new generation of recombinant products have been developed and research is underway into the development of other complex or hybrid blood products. As the dynamics of globalisation and modernisation engage the way that blood services are organised, the tasks facing regulators and policy-makers have become more complex. The paradox in the long endeavour to supply safe blood - that new risks have emerged or been manufactured, even as progress is achieved- resonates with wider sociological discussions about the nature of risk in modern societies. The project methods include socio legal analysis and qualitative methods such as interviews, which will generate new empirical data on the perspectives of patients, professionals, and policy makers about risk and safety in the supply of blood and blood products.